(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Activated carbon (AC) was prepared by the conventional carbonization and KOH activation and amorphous silica was extracted by alkali extraction followed by acid precipitation from rice husk on a laboratory scale. The performance of the produced activated carbon and amorphous silica were examined using I2 value measurement, methylene blue (MB) adsorption test, pH measurement, FTIR and SEM-EDX analysis. The optimum temperature for production of AC was obtained at 700 0C. The AC by alkali extraction method was show higher activity than KOH activation. The maximum I2 value, MB adsorption value & pH value shows at 700 0C followed by alkali extraction with 15% NaOH, which were 510.82 mg/g, 61.1 mg/g and 7.32 respectively. The FTIR analysis shows presence of Si-O-Si bond with a strong peak at 1078.28 cm-1. The SEM image of silica sample shows that the most of organic component is burnt out during combustion. Bangladesh J. Sci. Ind. Res. 50(4), 263-270, 2015